Effect of Rapamycin on MOG-Reactive Immune Cells and Lipopolysaccharide-Activated Microglia: An in Vitro Approach for Screening New Therapies for Multiple Sclerosis - Borim, Patricia Aparecida [UNESP] (2022)
Rapamycin is an immunomodulatory drug that has been evaluated in preclinical and clinical trials as a disease-modifying therapy for multiple sclerosis (MS). In this study, we evaluated the in vitro effect of rapamycin on immune cells pivotally involved in the pathogenesis of experimental autoimmune encephalomyelitis (EAE), which is an animal model to study MS. Splenocytes and central nervous system (CNS)-mononuclear cells obtained from EAE mice were stimulated with a myelin oligodendrocyte glycoprotein peptide, whereas the microglial BV-2 cell line was activated with LPS. The 3 immune cell types were simultaneously treated with rapamycin, incubated, and then used to analyze cytokines, transcription factors, and activation markers. Rapamycin reduced IL-17 production, TBX21, and RORc expression by splenic and CNS cell cultures. IFN-γand TNF-α production were also decreased in CNS cultures. This treatment also decreased TNF-α, IL-6, MHC II, CD40, and CD86 expression by BV-2 cells. These results indicated that in vivo immunomodulatory activity of rapamycin in MS and EAE was, in many aspects, reproduced by in vitro assays done with cells derived from the spleen and the CNS of EAE mice. This procedure could constitute a screening strategy for choosing drugs with therapeutic potential for MS.